Analysis on Cashless Transactions using E-Wallet among Adults in Malaysia: A Correspondence Analysis Approach - Tan, Ye Wen; Che Him, Norziha; Abd Latif, Noor Azliza; Yusof, Yusliandy (Enhanced Knowledge in Sciences and Technology, 2025)
The rapid advancement of technology and the rise of digital transformation have shifted consumer behaviour toward cashless payment systems, particularly e-wallet. This study aims to identify the most preferred e-wallet platform and determine usage purposes by descriptive analysis and examining factors influencing adoption using correspondence analysis (CA). A survey conducted at Universiti Tun Hussein Onn Malaysia (UTHM) collected data from 396 respondents via convenience sampling. The results revealed that Touch ‘n Go eWallet as the most preferred platform (89.9%), with convenience cited as the primary usage purpose (95.49%). A strong association between factors and agreement levels was examined and confirmed by employing CA, with a p-value of less than 0.001 from the Chi-Square test of independence. Meanwhile, the first two dimensions explain 99.86% of the total variation in the data. Notably, Perceived Usefulness (PU) contributes most to Dimension 1 (56.58%) and Perceived Risk (PR) to Dimension 2 (40.61%). These findings highlight the dominance of Touch ‘n Go eWallet and underscore the importance of addressing security concerns to further encourage e-wallet adoption in Malaysia. They also provide actionable insights for e-wallet service providers and policymakers to improve app features, enhance user experience and address user challenges by understanding usage purposes and identifying key issues faced by users.